SAFFA-NG Sistem Aristektur Manajemen Kasus Forensik - Wiryana MSc, I Made; Mutiara, Dr. A.B.; Suhendra, Dr. A.; Hadibowo, R.; Vangerow, Andreas (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 1 (2008): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/10.24843/IJLFS.2008.v01.i01.p03)
Cybercrime has been known as side effects of the use of ICT. The character of digital evidences which are veryspecific, require special handling methods. Nowadays, there are many forensics tools which are either proprietary oropen source. However, most of them are low level tools which are used to gather the uncover data from the storage orcomputing devices. A better forensic case management which support the root cause analysis based on a formal methodwill assist the work of investigator. SAFFA-NG is a freely available workflow system which is designed to assist thework of forensic and investigator by guiding the forensic work according to forensic guidelines. SAFFA-NG is developedusing many Open Source Software components which ensure the thorough auditing of the system. It is designed basedon technical and forensic requirements. This is a collaboration projects between Gunadarma University, IMade Wiryana (RVS Arbeitsgruppe – Bielefeld University) and Andreas Vangerow (P3 Consulting GmbH).During the development of system some feedbacks and assistance are provided by LKA Niedersachsen, KPKand Indonesia Police Department.
Keywords: Computer Forensic, Case management, Open Source.